Herbal Support for the Nervous System: The Impact of Adaptogens in Humans and Dogs - Jagoda Kępińska-Pacelik; Wioletta Biel (Applied Sciences)
Plants have played a key role in natural therapies for centuries, and their impact on the nervous system and the treatment of neurological disorders is of growing interest to scientists. Modern research confirms that plant substances can modulate neurotransmitters, reduce oxidative stress and support cognitive functions. Like humans, dogs also respond to plant compounds, which opens up new perspectives in veterinary medicine. The most well-known adaptogen is ginseng, and others include Siberian ginseng, Chinese magnolia vine, maral root, and golden root. These plants support the regulation of cortisol levels, neurotransmission and neuroplasticity. Although research on adaptogens in humans is advanced, there is still a lack of data on their effects on dogs. Further research is necessary to confirm their effectiveness and safety in animal therapy.